2008
DOI: 10.1364/oe.16.016151
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and myosin characterization by orientation field second harmonic microscopy

Abstract: Collagen and myosin fibrils are endogenous harmonophores that both give rise to Second Harmonic Generation (SHG). By combining four polarization SHG images provided by a scanning microscope, we show that the orientation of the principal axis of the nonlinear susceptibility tensor chi(2) can be determined for each pixel of the image. The ratio rho = chi33/chi15 of the principal components of chi(2) of collagen and myosin was obtained with the same method, and found within the range 1.6-1.8 and 0.5-0.6 respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 25 publications
7
77
1
Order By: Relevance
“…SHG microscopy is a powerful tool to image intrinsic subcellular signals from endogenous well-ordered proteins such as tubulin, myosin and collagen [24][25][26][27]. Concerning myosin, coherent emission from myosin molecules of thick filaments is responsible of the characteristic periodical sarcomeric SHG signal observed in striated muscles [28][29][30][31][32][33][34][35][36][37][38][39]. We have previously shown that the canonical single frequency (1f) sarcomeric SHG intensity pattern (SHG-IP) is converted to double frequency (2f) sarcomeric SHG-IP in xenopus muscle when concentration of reactive oxygen species (ROS) increases [40].…”
Section: Introductionmentioning
confidence: 99%
“…SHG microscopy is a powerful tool to image intrinsic subcellular signals from endogenous well-ordered proteins such as tubulin, myosin and collagen [24][25][26][27]. Concerning myosin, coherent emission from myosin molecules of thick filaments is responsible of the characteristic periodical sarcomeric SHG signal observed in striated muscles [28][29][30][31][32][33][34][35][36][37][38][39]. We have previously shown that the canonical single frequency (1f) sarcomeric SHG intensity pattern (SHG-IP) is converted to double frequency (2f) sarcomeric SHG-IP in xenopus muscle when concentration of reactive oxygen species (ROS) increases [40].…”
Section: Introductionmentioning
confidence: 99%
“…The SHG signal rendered from the use of high-intensity fs pulses upon nonlinear media have brought advances in the diagnostics of tissue structure rich in collagen and myosin. 8,21,28 Since 1986, the application of scanning second harmonic microscopy has revealed polarization of filamentous, columnar structures of collagen fibril in native rat tail tendons, which exhibit the directionality that permeate the tendon cross-section. 37 Since then, SHG microscopy, a complementary, structuresensitive tool to MPFM, has found enormous usefulness in optical tissue biopsy and reconstruction of intact structure of mammalian tissues, as well as in the study of local cellular membrane morphology and its dynamics, which were previously unattainable with conventional histology.…”
Section: Basis Of Shg Origin In Biological Mediamentioning
confidence: 99%
“…Specifically, fs, NIR laser-induced nonlinear optical processes have proven viable imaging techniques for extracting contrast-specific signature of biological structures, such as molecular arrays of myosin, collagen, and lipid, allowing investigation of tissue structure and its organization as well as physiopathology of tissues at the cellular and molecular levels. [7][8][9] Since nonlinear optical processes can be registered with excitation intensity in the range of 10 6 to 10 8 W∕cm 2 , 10,11 such stringent requirements for photon flux limit excitation as well as the fluorescent signal collection to the focal volume and provides corresponding lateral and axial resolutions of around 220 and 520 nm, respectively, when focusing a 900-nm laser beam with a 1.2 numerical aperture objective lens. 12 To further improve contrast and sensitivity, laser-scanning multiphoton excitation fluorescence microscopy (LS-MPFM) has been combined with other optical modalities such as life-time imaging 13 and phase-contrast microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the myosin filaments have a noncentrosymmetric structural organization, muscle tissues can be imaged using Second Harmonic Generation (SHG) microscopy [6][7][8][9][10][11][12][13][14][15][16]. Other biological structures possess a noncentrosymmetric organization such as tissues rich in collagen type I/III proteins [14][15][16][17][18][19][20][21][22], collagen type 2 [22][23][24] and the microtubules within cells [25].…”
Section: Introductionmentioning
confidence: 99%
“…Other biological structures possess a noncentrosymmetric organization such as tissues rich in collagen type I/III proteins [14][15][16][17][18][19][20][21][22], collagen type 2 [22][23][24] and the microtubules within cells [25]. SHG microscopy is a powerful technique to image those samples as it provides submicron spatial resolution and is free of photobleaching as the signal arises from an organized structural arrangement lacking a center of inversion.…”
Section: Introductionmentioning
confidence: 99%